Crecimiento y supervivencia de plántulas de Welfia georgii en un bosque pluvial en la costa caribeña de Costa Rica - Vandermeer, John (Universidad de Costa Rica, 1990)
Seedlings of the palm Welfia georgii were studied at the La Selva biological station in the Atlantic coast of Costa Rica during the years 1973 -1976. The distribution of sizes of seedlings corresponds qualitatively 10 what is expected. There were few seedlings larger than 4.5 cm, representing individuals that already had been exposed 10 a light gap and which therefore had grown rapidly. The majority of the individuals in the population had been degrowing due 10 their position in the understory. The general survivorship of seedlings was 61 %. The mean of the rate of growth was approximately -0.09 cm/año (the mean of the width of lcaflets) a statistic which may leave a false impression. The rate of growth is related to the size of the seedling in a complicated non-linear manner, in which very small individuals grow relatively rapidly, intermediate individuals "degrow" (actually decrease in size over time), and larger seedlings also grow rapidly. Using a model modified after Leflkowitch it is observed that the population of seedlings appears 10 be stable in the distribution of stages.